Effect of moderate electric fields in the permeation properties of chitosan coatings - Souza, B. W. S. (2009)
Edible films and coatings can provide additional protection for food, while being a fully biodegradable, environmentally friendly packaging system. Preliminary works have shown that the presence of a moderate electric field during the preparation of chitosan coating solutions may influence e.g. their transport properties. If such effect is confirmed, moderate electric fields could be used to tailor edible films and coatings for specific applications. The aim of this work was to determine the effect of field strength on functional properties of chitosan coatings (obtained from lobster from the Cuban coasts). Four different field strengths were tested (50, 100, 150, 200 V cm−1) and, for each electric field treatment, the water vapor, oxygen and carbon dioxide permeabilities of the films formed were determined, together with their color, opacity and solubility in water. The surface microstructure of the films was analyzed using atomic force microscopy (AFM). The results showed that ohmic heating had statistically significant effects on film's physical properties and structure. In general, the most pronounced effect of the field strength was observed for treatments made at 100 V cm−1 or higher, a positive correlation being found between the water vapor, oxygen and carbon dioxide permeability coefficients and field strength. The AFM results show that the surface of chitosan films is much more uniform when an electric field is applied, which may be related with a more uniform gel structure leading to the differences observed in terms of transport properties.